Evaluasi Program Kebun Gizi oleh Dompet Dhuafa Nusa Tenggara Timur dalam Pemberdayaan Masyarakat di Dusun Neken Desa Billa Kabupaten Timor Tengah Selatan (Lembaga Pengembangan Kinerja Dosen, 2026)
Stunting and nutritional vulnerability remain major challenges in Indonesia, particularly in underdeveloped regions such as Timor Tengah Selatan Regency, East Nusa Tenggara Province. Efforts to reduce stunting require not only government interventions but also the active involvement of non-governmental organizations through community empowerment approaches. This study aims to evaluate the implementation of the Nutrition Garden Program conducted by Dompet Dhuafa East Nusa Tenggara in Neken Hamlet, Billa Village, as a community-based strategy to strengthen food security and nutrition. This research employs a descriptive qualitative approach using the CIPP evaluation model (Context, Input, Process, Product). Data were collected through observation, semi-structured interviews, and documentation involving eight key informants, including program managers, community leaders, health workers, and beneficiary households. The findings indicate that the Nutrition Garden Program is relevant to community needs, supported by adequate resources and funding, and implemented through a participatory approach. The program has contributed to improving access to nutritious food, enhancing agricultural knowledge, and supporting household economic resilience, as well as indirectly contributing to stunting prevention, although its impact has not been evenly distributed. Key challenges include limited infrastructure, inadequate access to water and electricity, marketing constraints, and weak administrative record-keeping. Overall, the Nutrition Garden Program is considered feasible to continue and has strong potential for sustainability with strengthened mentoring, infrastructure development, and cross-sector collaboration.